Put-call parity in Indian stock markets post turmoil settlement - Pankaj Kumar Gupta (Trends Economics and Management, 2018)
Purpose of the article: Put and call prices have a deterministic relationship for identical options irrespective of the investor dmand. The theoretical put-call parity (PCP) relationship may be analysed to explore the arbitrage opportunity and determine the extent of market efficiency. We have studied the violation of this relationship using a case of options traded on the National Stock Exchange of India (NSE) on various parameters including Moneyness, arbitrage differential, and time to maturity and trade volumes. Methodology/methods: We use regression models with dummy variables on one-year sample data (Jan-Dec 2017) of the NSE Nifty Call and Put options to examine the existence of arbitrage indicating the inefficiency of market particularly the illiquidity factor. In the selected period (turmoil settlement), the relative volatility is low and it is worth testing the PCP. Scientific aim: The aim of this research is to improve the knowledge on market efficiency in developing markets highlighting the role of major market participants. Findings: We have found that the violation of the put-call parity relationship in a large number of cases occurred even during the post turmoil settlement period. Arbitrage profits are found to be significant for deeply in-the-money and deeply out-of-the money options though the differentials are not significantly affected by the increase or decrease in time to maturity and liquidity indicating a direct relationship. Also, the gap between the spot price and the strike price of the Nifty index options is directly proportional to the arbitrage profit. Conclusions: We have established that in options markets, significant arbitrage opportunities exist violating the Put-Call parity relationship even in the times of low volatility and relatively higher trade volumes. For the policymakers, the immediate concern is to improve the market competitiveness.
Keywords: D53; G12; 650; Put-Call Parity; Arbitrage Profit; Moneyness; NIFTY; Liquidity